Single and combined effect of kinesio tape and warm-up on sprint cycling performance - Alessio Rossi; Damiano Formenti; Luca Cavaggioni; Giampietro Alberti; Fabio Esposito; Fabio D'Angelo; Athos Trecroci (BMC, 2021)
Abstract Background The fact that kinesio tape may be capable to enhance muscle power would qualify it as practical tool to be considered during passive warm-up (WU) or coupled with active WU processes prior to power-based performance. Therefore, the aim of this study was to investigate the single and combined effect of kinesio tape (KT) and WU on sprint cycling performance. Methods In a repeated measure design, fifteen participants underwent six sessions to assess sprint cycling performance involving a combination of three taping conditions (without KT: NoKT; with KT positioned vertically over the thigh muscles KT; with KT positioned horizontally over the thigh muscles: Sham) with two pre-exercise routines (with WU: WU; without WU: NoWU) in a randomized order. Allometric scaling of peak power (PP) and average power (AP) values were considered for each sprint. Results KT-WU demonstrated the highest PP and AP with respect to the other conditions (p < 0.05), except for AP that was similar to Sham-WU (p > 0.05). Moreover, NoKT-NoWU showed the lowest PP and AP with respect to the other conditions (p < 0.05). Conclusions Overall, our findings suggest that kinesio tape might be a possible tool to be combined with an active WU routine, inducing benefit on sprint performance. Moreover, KT may be considered a potential strategy to include within a passive WU, perhaps where an active WU is not feasible. However, as the influence of KT on muscle function is still unclear, our results should not be overinterpreted.